The Flavonoid 7, 4′‐Dihydroxyflavone Inhibits MUC5AC Gene Expression, Production, and Secretion via Regulation of NF‐κB, STAT6, and HDAC2. (23rd March 2015) - Liu, Changda; Weir, David; Busse, Paula; Yang, Nan; Zhou, Zhenwen; Emala, Charles; Li, Xiu‐Min
<x xml:space="preserve">Abstract</x> Mucus overproduction is a significant component of the pathophysiology of obstructive lung diseases. Currently, there are only a few medications available that inhibit mucus production. Previous studies showed that glycyrrhizin, a triterpenoid in Glycyrrhiza uralensis inhibits mucin 5AC (MUC5AC) mRNA and protein expression. Other potential mucus production inhibitory compounds contained within in G. uralensis have not been fully investigated. The aim of the present study was to determine if the G. uralensis flavonoid 7, 4′‐dihydroxyflavone (7, 4′‐DHF) inhibits MUC5AC gene expression, mucus production, and secretion, and if so, to elucidate the mechanism of this inhibition. 7, 4′‐Dihydroxyflavone significantly decreased phorbol 12‐myristate 13‐acetate‐stimulated NCI‐H292 human airway epithelial cell MUC5AC gene expression and mucus production, at a 28‐fold lower concentration than glycyrrhizin (The half maximal inhibitory concentration IC50 value of 1.4 μM vs 38 μM, respectively); 7, 4′‐DHF also inhibited MUC5AC mucus secretion. Inhibition was associated with the suppression of nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB), signal transducer and activator of transcription 6 (STAT6) activation, and enhanced histone deacetylase 2 (HDAC2) expression. In a murine model of asthma, 7, 4′‐DHF‐treated mice exhibited a marked reduction in MUC5AC secretion in the bronchoalveolar lavage fluid compared with control mice. These findings, together with previous findings linking NF‐κB, STAT6, and HDAC2 modulation to the control of MUC5AC expression, demonstrate that 7, 4′‐DHF is a newly identified component of G. uralensis that regulates MUC5AC expression and secretion via regulation of NF‐κB, STAT6, and HDAC2. Copyright © 2015 John Wiley & Sons, Ltd.